An Open-Source User Interface Development for Widely Used Low-cost Spectrometer Designs - GÜRKAN, GÜRAY (Istanbul Univ., 2020)
In this paper, the development and test stages of an open-source user interface are presented. The developed user interface is compatible with most of the low-cost camera-based spectrometer designs in the literature. The spectrum image of the light source that is acquired with the camera is cropped and analyzed in a real-time thread after interactive calibration which is a special feature of the user interface. Camera controls (such as brightness, contrast, saturation, exposure and etc.) are also available through the user interface. For user interface testing, a common spectrometer design that is composed of a light-guide tube with a narrow entrance slit in one end and an image sensor on the other is constructed. Various compact fluorescent lamps and light emitting diodes are applied as light source and the results are presented. Developed cross-platform user interface can be used with lowcost spectrometer designs especially involving a web camera.
Keywords: Grating Material; Image Processing; Open Source; Python Programming; User Interface Design